General provisions of the contract on hotel services - Федорченко, Н. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article deals with concepts and general provisions of the contract on hotel services, issues of concern to provide hotel services.